Aktivitas harian lumba-lumba hidung botol Indo-Pasifik (Tursiops aduncus) rehabilitasi di Umah Lumba, Teluk Banyuwedang, Bali - Sulthanah, Hafshah Aliyah; Yusup, Deny Suhernawan; Yuni, Luh Putu Eswaryanti Kusuma (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i01.p11, 2024)
Study on the daily activities of confiscated animals prior to be released is very important for the success of an animal release program. This research focuses on confiscated bottlenose dolphins Tursiops aduncus which were rehabilitated in Umah Lumba, Banyuwedang Bay, Pejarakan Village, Gerokgak District, Buleleng, Bali, and aims to determine the daily activities of bottlenose dolphins in Umah Lumba prior to be released in North Bali waters. Observations of daily activities was carried out by using the focal animal sampling method with instantaneous recording on three individual bottlenose dolphins in Umah Lumba. This study showed that there were several activities that support life in the wild, namely the absence of tail clapping activity, as well as the locomotion and breathing activities increased optimally. Likewise, it was also recorded the activities that indicated the optimal condition of their physiological state, such as a minimal sneezing activity and recorded jumping activity as one of the foraging strategies carried out by dolphins in their natural habitat. Those activities are improvements towards optimal conditions ahead of release from the observation conducted at the beginning of the rehabilitation period.